2015
DOI: 10.15446/esrj.v19n2.49372
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic Evolution and Compositional Characteristics of Tertiary Volcanic Rocks Associated with the Venarch Manganese Mineralization, Sw Qom, Central Iran

Abstract: The manganese (Mn) deposits of Iran date from late Proterozoic to Pliocene but the major high-grade Mn ore deposits are associated with tertiary basic to intermediate volcanic rocks. The Venarch Mn deposit is located in the SW Qom city and considered as one of the largest in Iran. The Mn mineralization is mostly hosted by Eocene high-k volcanic and pyroclastic rocks of Urmia-Dokhtar Magmatic Arc (UDMA). The study area mainly consists of basalt, trachybasalt, andesite, and basaltic-andesite that are intruded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…type of host rock and soil) plays a remarkable role in variable of radioactivity reaction, as much as the type of water resources [35]. According to Mahdavi et, al., fault zones appeared in this type of soil (in Qom) [36], while another study showed that there is a relationship between radon concentration and the presence of faults [6]. These may be the reasons for the highest radon concentration in the ATB soil in Qom.…”
Section: Resultsmentioning
confidence: 96%
“…type of host rock and soil) plays a remarkable role in variable of radioactivity reaction, as much as the type of water resources [35]. According to Mahdavi et, al., fault zones appeared in this type of soil (in Qom) [36], while another study showed that there is a relationship between radon concentration and the presence of faults [6]. These may be the reasons for the highest radon concentration in the ATB soil in Qom.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the basis of the method involves calculating the stress distribution at the time of fracture generation using all structural data including: faults, fractures and folds, rock characteristics, and tectonic events. Also, secondary activities, such as mineralization and rock inclusions are essential, especially for mining exploration (Mahdavi et al, 2015). The main components of the forward geomechanical restoration model are: (1) the initial condition of paleo-geometry, (2) the constitutive laws of sedimentary units, and (3) boundary constraints.…”
Section: Introductionmentioning
confidence: 99%